2021
DOI: 10.1016/j.ijchp.2020.09.001
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study on depressive symptoms and physical activity during the Spanish lockdown

Abstract: Background/Objective : The aim was to evaluate the evolution of depressive symptoms and to explore the influence of physical activity (PA) practice during the home confinement due to the COVID-19 outbreak in Spain. Method : Information was collected from 595 confined participants who reported personal and contextual information, depressive symptoms and PA levels at four time points. Results : The changes in depressive symptoms were analyzed using a linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 29 publications
3
42
0
8
Order By: Relevance
“…This could be related to differences in the socio-cultural contexts faced by different populations and/or differences between countries. However, other longitudinal studies carried out in Spain have reported a significant increase in depressive symptoms, both between subjects and within subjects, during the first weeks of lockdown, though there is no consensus regarding the progression of anxiety [ 34 , 40 , 41 ]. The differences between these studies could be due to the different scales they used to measure anxiety and depression, their cut-off points, their design, or the range of periods considered.…”
Section: Discussionmentioning
confidence: 99%
“…This could be related to differences in the socio-cultural contexts faced by different populations and/or differences between countries. However, other longitudinal studies carried out in Spain have reported a significant increase in depressive symptoms, both between subjects and within subjects, during the first weeks of lockdown, though there is no consensus regarding the progression of anxiety [ 34 , 40 , 41 ]. The differences between these studies could be due to the different scales they used to measure anxiety and depression, their cut-off points, their design, or the range of periods considered.…”
Section: Discussionmentioning
confidence: 99%
“…In the current literature there is substantial debate about the detrimental effects of pandemic fatigue. In particular, there are two major views: some longitudinal studies supported the theory that adverse effects have intensified as time in lockdown increased and showed significant increments in negative symptoms such as depression, anxiety, or stress (Ausín et al, 2021;Cecchini et al, 2021;Gopal et al, 2020). In contrast, other studies argued that the effects did not increase over time and, in any case, were are greater at the beginning of the pandemic due to uncertainty and fear of the unknown situation (Canet-Juric et al, 2020).…”
Section: Effects Of Pandemic Fatiguementioning
confidence: 99%
“…As the pandemic has progressed, teachers and universities have been adapting and have implemented several innovations to improve the online teaching experience of students (Scull et al, 2020). On the other hand, the variables related to the social aspects of the academic experience, such as the contact with other students and teachers, may be negatively affected by the feeling of burnout as time in lockdown passes (Ausín et al, 2021;Cecchini et al, 2021;Gopal et al, 2020). As other studies have reported, the lockdown situation has triggered the feeling of isolation and disconnection of students (Al-Balas et al, 2020;Puljak et al, 2020;Son et al, 2020), feelings already identified in pedagogical research on the challenges of e-learning (Mcinnerney & Roberts, 2004).…”
Section: Effects Of the Prolonged Lockdown On Students' Learning Experiencementioning
confidence: 99%
“…During the first wave of the COVID-19 pandemic, several studies have investigated its mental health consequences in the Spanish adult population (Gonzalez-Sanguino et al, 2020;Cecchini et al, 2021;Garcia-Fernandez et al, 2020;Losada-Baltar et al, 2021;Planchuelo-Gomez et al, 2020;Justo-Alonso et al, 2020;Pérez et al, 2020;Balanzá-Martínez et al, 2020;Valiente et al, 2021;Mortier et al, 2021).…”
Section: Introductionmentioning
confidence: 99%